Effects chemical disinfectants on surface roughness of conventional impression materials used for dental prosthetic procedures - Altintas, E.; Rencber, A. (Wolters Kluwer Medknow Publications, 2022)
Background to Aim: To compare the effects of disinfectants on surface roughness of the conventional impression materials following chemical disinfection procedures. Materials and Methods: Equal numbers (65 for each impression material) of disc-shaped (15 × 3 mm) samples (Total n = 195) were fabricated from polyvinyl siloxane (Zhermack Elite), polyether (3M Impregum Penta Soft), and vinyl siloxane ether (Kettenbach Identium Lightbody) impression materials. Each impression material group was divided into five subgroups including one control group (n = 13). Impression material samples were immersed in CaviCide for 3 min, Zeta 7 solution for 10 min, and 5.25% sodium hypochlorite solution for 3 and 10 min. Surface roughness (Ra) was measured using a profilometer (Mitutoyo-SJ 410, Mitutoyo Corp.). The study data were analyzed statistically. Results: A statistically significant difference was found among impression materials and disinfectants in terms of surface roughness (P < 0.05). Polyvinyl siloxane material showed a lower Ra value compared to Polyether and VSE materials; while polyether material showed a significantly lower Ra value compared to VSE material. Ra values of the control group were significantly lower than the disinfectant group immersed in 5.25% NaOCl solution for 10 min. Conclusion: Among all impression materials, polyvinyl siloxane showed the least surface roughness following disinfection procedures. Impression disinfectants that are specially designed for disinfecting dental impressions resulted in less surface roughness in all impression materials. With this study, it was aimed to obtain a smooth and clear model for the production of correct and compatible prostheses in the laboratory while at the same time purifying the impressions from microorganisms. © 2022 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Conventional; disinfection; impression materials; surface roughness